Perilaku Perempuan dalam Menentukan Pilihan Politik pada Pemilu DPRD Kota Medan 2014 - M HABIBIE FITRAWAN HASIBUAN; T. IRMAYANI (Universitas Sumatera Utara, 2017)
The representation of women is one of the most highlighted in the general elections in Indonesia in the last period.This is because the representation of women in the legislature is very minimal. This study describe female behavior in determining political choices in the legislative election in 2014. Especially at dapil 2 (electoral district) in the Kota Medan. The findings of the study is there are three approaches that can see and analyze how the behavior of voters (women) determine the political choices in elections. First, sociological approach; Second, a psychological approach; Thirdly, the approach of rational voters.Female voter behavior influenced the figures and the track record of candidates,there is a tendency to choose the incumbent candidates, independently, saw the vision, mission, or the track record of candidates. The study used the approach to political ideology. This study method is descriptive. Collecting data with depth interview. Analysis of data using qualitative analysis.